SPECTRUM OF SOMATIC MUTATIONS IN RETROPERITONEAL LEIOMYOSARCOMA: CLINICAL CASE AND LITERATURE REVIEW - V. E. Bugaev; M. P. Nikulin; D. A. Golovina; V. M. Safronova; S. N. Nered; L. N. Lyubchenko; I. S. Stilidi (Сибирский онкологический журнал)
Retroperitoneal leiomyosarcomas (RpLMS) are highly aggressive tumors, which are characterized by poor prognosis and resistance to chemotherapy. Targeting tumor-specific molecular pathways have become a rapidly expanding field in drug development to increase efficacy of treatment of LMS. Here we present a case report of rapidly progressive RpLMS with gene mutations of key molecular pathways, which have not previously described in the literature. A 61-year-old man was admitted to our hospital with complaints of abdominal pain and fever. Radiological examination revealed retroperitoneal leiomyosarcoma, which was histologically confirmed by core-biopsy. The patient underwent radical (R0) en-bloc resection of tumor with left hemicolectomy, left total nephrectomy, left total adrenalectomy and distal subtotal pancreatectomy. Pathological assessment of the tumor revealed G3 leiomyosarcoma. The patient did not receive adjuvant therapy. Disease progression (local recurrence and pulmonary metastases) occurred 3 months after surgery, and the patient died 6 months after surgery. Immunohistochemical study revealed positive PD -L1 expression in tumor cells. The percentage of PD -L1- expressing cells was 30 %. Molecular-genetic testing allowed identification of somatic mutations in genes, such as PIK3CA, ALK, EGFR, ERBB, ESR1 and PD GFRA and confirmation of microsatellite stable status (MSS) of the tumor. Further studies to investigate spectrum of mutations in RpLMS are of great interest, since they can allow identification of potential targets for more effective antitumor therapy and to improve treatment results.